MEANINGFUL ACTIVITIES AND MEANING IN LIFE IN SOUTH KOREA: BASIC PSYCHOLOGICAL NEEDS SATISFACTION AS AN EXPLANATORY MECHANISM - SaeMi Park (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2023)
Introduction – The self-determination theory implies that autonomy, relatedness, and competence might influence the extent to which one perceives his/her life is meaningful. In addition, we examined whether the level of engagement in meaningful activities is subject to the satisfaction of basic psychological needs, which in turn is likely to form perceptions on a meaning in life. Methods – To address these questions, we analyzed survey data that is collected from South Korean adults at the individual level in March of 2023 (N=36). I conducted t-tests and a zero-order correlation before working on the serial mediation analysis. PROCESS macro model 80 is used to analyze serial meditation mechanisms including exposures to meaningful activities, basic psychological needs satisfaction, engagements in meaningful activities, and meaning in life. Results – The serial mediation model discovers two significant paths involving that higher levels of sense of autonomy have increased perceptions on a meaningful life. Also, once individuals regularly participate in meaningful activities, a sense of relatedness is shown to be enhanced. Discussion – This research can contribute to the study of public health by suggesting that beneficial psychological effects of engagement in meaningful activities have subsequent social implications through an increased sense of belongingness. More one senses autonomy, the more likely hold meaningful life perceptions. Participation in meaningful activities has to do with an increase in a sense of relatedness. Conclusion – Autonomy has a significant direct effect on meaningful life perception, which corroborates satisfaction with autonomy plays an important role in the South Korean population’s well-being. By designing initiatives is likely to enjoy greater levels of satisfaction in a sense of relatedness, implying an improved sense of belongingness to one’s network, including their neighborhood and society. Keywords: meaningful activities, autonomy, relatedness, competence, meaning in life.